The Cambridge guide to literature in English - Ousby, Ian, 1947- (Cambridge University Press, 1988)
"Substantially enlarged and updated, this new edition of The Cambridge Guide to Literature in English confirms its status as the most authoritative survey of its subject now available in a single volume. Its coverage of novelists, poets, playwrights and their works embraces both the established classics of English literature and a wealth of contemporary figures from all over the English-speaking world, such as Saul Bellow, Adrienne Rich, Les Murray, Wole Soyinka, R.K. Narayan, Janet Frame, Mordecai Richler, Joseph Brodsky, J.M. Coetzee and Ben Okri." "Under Ian Ousby's editorship over a hundred contributors provide detailed biographical and critical articles, not only about writers and works of literature, but also about the critics, philosophers, historians and biographers who have influenced or reacted to literature. Substantial coverage is given to popular genres such as science fiction, detective novels and children's literature, with entries on, for example, Dr. Seuss, Margaret Mahy, Roald Dahl, Isaac Asimov, Frederik Pohl, P.D. James and Nicolas Freeling." "Other entries range widely over literary groups and movements, critical schools, genres, poetic forms, critical concepts, rhetorical terms, literary terms, theatres and theatre companies. There are also substantive articles on subjects such as copyright, libraries and the English language." "With a superb range of illustrations and a comprehensive cross-referencing system, The Cambridge Guide to Literature in English is both an outstanding reference book, and a delightful companion for anyone who enjoys reading."--Jacket. Substantially enlarged and updated, this new edition of The Cambridge Guide to Literature in English confirms its status as the most authoritative survey of its subject now available in a single volume. Its coverage of novelists, poets, playwrights, and their works embraces both the established classics of English literature and a wealth of contemporary figures from all over the English-speaking world, such as Saul Bellow, Les Murray, R. K. Narayan, Mordecai Richler and Ben Okri.